2019
DOI: 10.1101/580423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in phosphorus and sulfur content shapes the genetic architecture and phenotypic associations within wheat grain ionome

Abstract: Summary Dissection of the genetic basis of wheat ionome is crucial for understanding the physiological and biochemical processes underlying mineral accumulation in seeds, as well as for efficient crop breeding. Most of the elements essential for plants are metals stored in seeds as chelate complexes with phytic acid or sulfur‐containing compounds. We assume that the involvement of phosphorus and sulfur in metal chelation is the reason for strong phenotypic correlations within ionome. Adjustment of element conc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Members of NRT1/PTR family of proton-coupled transporters, which are involved in nitrogen metabolism in different plant species (Fang et al 2013; Naz et al 2017; Castro-Rodriguez et al 2017; Corratge-Faillie and Lacombe 2017) and, hence, influencing protein accumulation, were identified within five QTL intervals in the S×Y population and were selected as promising CGs. Sulfur metabolism was shown to be an important factor that can alter nitrogen accumulation (Howarth et al 2008; Dai et al 2015; Bonnot et al 2017), following this idea glutamate and glutathione related CGs were identified within intervals of seven QTLs in the S×Y population and also was shown for QTLs in the L×G population (Fatiukha et al 2019b).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Members of NRT1/PTR family of proton-coupled transporters, which are involved in nitrogen metabolism in different plant species (Fang et al 2013; Naz et al 2017; Castro-Rodriguez et al 2017; Corratge-Faillie and Lacombe 2017) and, hence, influencing protein accumulation, were identified within five QTL intervals in the S×Y population and were selected as promising CGs. Sulfur metabolism was shown to be an important factor that can alter nitrogen accumulation (Howarth et al 2008; Dai et al 2015; Bonnot et al 2017), following this idea glutamate and glutathione related CGs were identified within intervals of seven QTLs in the S×Y population and also was shown for QTLs in the L×G population (Fatiukha et al 2019b).…”
Section: Discussionmentioning
confidence: 94%
“…QTL analysis of the L×G RIL population revealed 8 loci with WEW alleles that conferred increased GPC, using low-density SSR-based map (Peleg et al 2009). Further analysis, using high resolution SNP-based map, expanded the number of loci with contribution of WEW alleles from 8 to 14 (Fatiukha et al 2019b). The identification of common or meta-QTLs between independent populations can help to improve QTL interval confidence, as demonstrated by Quraishi et al (2017), and can be used for confirmation of detected effects in different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation